Yerba Mate: The Natural Boost Your Body Craves - Draim, Malwina; Rostkowska, Aneta; Kupisiak, Sebastian; Pasierb, Natalia; Rękas, Barbara; Kosowska, Michalina; Dzierzgowska, Wiktoria; Latocha, Julia (Quality in Sport, 2025)
Introduction: Yerba Mate (Ilex paraguariensis) is a traditional South American infusion known for its stimulant and antioxidant properties. Historically consumed for its energizing effects, it was also regarded as a medicinal remedy by indigenous cultures, used to treat fatigue, stress and digestive issues [1, 2]. In recent decades, Yerba Mate has gained global recognition and has garnered scientific interest due to its potential health benefits such as improving cardiovascular health, metabolic function and supporting physical performance [1–5]. Its rich content of polyphenols, xanthines and saponins may contribute to a range of protective and restorative effects on the human body [1, 8]. Purpose of the work: The aim of this study is to evaluate existing research on the effects of Yerba Mate consumption on human health and athletic performance, with a focus on its antioxidant activity, metabolic support and cardiovascular benefits. Materials and methods: A comprehensive literature review was conducted using PubMed, Scopus, Google Scholar and Science Direct databases, encompassing clinical studies, randomized trials and relevant animal model research on the bioactive effects of Yerba Mate. Results: This review indicates that Yerba Mate may support lipid metabolism, reduce oxidative stress and improve cardiovascular markers [3–5, 7, 8]. Furthermore, its caffeine content and phytochemical profile may serve as a natural alternative to synthetic stimulants used by athletes [1, 5, 13]. Nonetheless, more rigorous clinical trials are needed to fully establish its efficacy and safety profile in athletic and general populations.